An Atypical Manifestation of Pheochromocytoma Crisis: Acute Delirium - Agarwal, M.; Kant, R.; Sharma, D.; Madan, S. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Pheochromocytoma is a rare neuroendocrine tumor presenting with a classical triad of symptoms. In 10% of the cases the presentation can be atypical, and the diagnosis is often missed for several years. Most common neurological manifestations are haemorrhage, seizures, etc., but pheochromocytoma crisis presenting as delirium has been infrequently reported. We present a case of a middle-aged female who presented with hypertensive emergency and acute confusional state. Other causes of delirium were ruled out in the patient and a timely diagnosis of pheochromocytoma was made with CT abdomen showed a large right suprarenal mass which was confirmed on 123I-MIBG scan and supported by elevated plasma metanephrines. She responded to alpha and beta blockers following which her blood pressure spikes were controlled and subsequently her sensorium improved significantly. Patient underwent surgical resection of the tumor and was followed up after 2 weeks with her blood pressure controlled without any medications.